Contribution of Agricultural Sector and Sub Sectors on Indonesian Economy - Refa’ul Khairiyakh; Irham Irham; Jangkung Handoyo Mulyo (Jurnal Ilmu Pertanian, 2015)
This research aimed to analyze trend of agricultural GDP and agricultural contribution in Indonesia, and identify the role of agricultural sector and sub sectors in provinces of Indonesia. Source of data this research use linear trend analysis to analyze trend agricultural Gross Domestic Product (GDP) and agricultural contribution. Location Quotient (LQ), Dynamic Location Quotient (DLQ), and combination LQ and DLQ is used to identify the role of agricultural sector and sub sectors. The analysis found that agricultural GDP in Indonesia has increasing trend while agricultural contribution has decreasing trend. Agricultural sector is basic sector in 29 provinces in Indonesia. Farm food crop is leading sub sector in 6 provinces, farm non food crops is leading sub sector in 14 provinces, livestock is leading sub sector in 3 provinces, forestry is leading sub sector in 1 provinces, fishery is leading sub sector in 5 provinces.